PlaneSpace : liberating employee innovative capacity - Kleinsmith, Niela; Koene, Bas, 1966-; Gautié, Jérôme (London : Rotterdam School of Management, Erasmus University, 2018)
This case highlights the long-term effects of major technological changes on a manufacturing organization and on the motivation and innovative potential of its employees. The case describes a 'lean' facility, which emphasizes Science and Technology-driven (STI) innovations, as opposed to Doing-Using-Interacting (DUI) innovations. The former is based on centralized, R&D-driven, codified knowledge and generally reflects a more rigid, hierarchical organizational structure. The latter is based on hands-on, or tacit, knowledge for problem-solving, and generally reflects informal communication lines and a more decentralized and horizontal organizational structure, typical of a 'learning' type of organization.
Originally Published In Kleinsmith, N., Koene, B., & Gautie, J. (2018). PlaneSpace: Liberating Employee Innovative Capacity. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Technological innovations -- Employee participation -- Case studies; Industrial management -- Case studies; Problem solving -- Case studies